Foresnsic and investigative accounting - Crumbley, D. Larry (CCH Incorporated, 2005)
The growing area of forensic accounting in which the knowledge, skills and abilities of advanced accounting are combined with investigative expertise and applied to legal problems. It covers both litigation support and investigative accounting and addition to examining the practical aspects of these two areas, as well as many of the newer technology. Explains and demonstrates: Investigative auditing techniques; Criminology; Courtroom procedures and more.